RARE CASE REPORT: SPINDLE CELL CARCINOMA WITH UNUSUAL METASTASIS TO THE BREAST - Malik, Shumaila Seemi; Shah , Syed Muhammad Hadi Ali; Nasir, Maheen; Malik, Safdar Ali; Malik, Fahad (Journal of Ayub Medical College Abbottabad, 2024)
Primary breast cancer is the most common malignancy in women, with metastatic involvement of the breast being quite an anomaly. Metastasis in the breast refers to cancer cells from elsewhere in the body, which infiltrate into the breast tissue. Spindle cell carcinoma is an aggressive subtype of sarcoma and is so named because of the characteristic spindle-shaped cells. Spindle cell carcinoma is a very rare type of cancer and accounts for only a few cancer cases as compared to adenocarcinoma or squamous cell carcinoma. However, due to its aggressive nature, it can rapidly spread to adjacent tissues and may even metastasize to distant organs including the lungs, gastrointestinal tract and as highlighted here; the breast. Case: We present the case of an 81-year-old female with the complaint of a painless nontender lump in the right breast for the last month. After proper investigations, a diagnosis of spindle cell carcinoma was confirmed. On CT chest, abdomen and pelvis for a proper workup for metastasis, an incidental note was made of a mass in the anterior right thigh. On further inquiry from the patient, it was found that the mass had been present for the last year but appropriate investigations had not been done. Fine needle aspiration (FNAC) and biopsy confirmed a diagnosis of spindle cell carcinoma of the right thigh, which had been missed in initial investigations. Conclusion: This case report highlights that in every patient who presents with a breast mass, proper clinical evaluation and diagnostic investigations are necessary to rule out the possibility of metastasis.